2019
DOI: 10.31223/osf.io/ercsv
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Machine learning on field data for hydraulic fracturing design optimization

Abstract: Growing amount of fracturing stimulation jobs in the recent two decades resulted in a significant amount of measured data available for construction of predictive models via machine learning (ML). Simultaneous evolution of machine learning has made it possible to apply algorithms on the hydraulic fracture database. A typical multistage fracturing job on a near-horizontal well today involves a significant number of stages. The post-fracturing production analysis (e.g., from production logging tools) reveals evi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…The application of data-driven approaches for the study of West Siberian shales was dedicated mostly to the characterization of geological and petrophysical properties of tight oil reservoirs. With respect to improved and enhanced oil recovery methods, most of the research was dedicated to optimization of hydraulic fracturing techniques [145][146][147][148]. A summary of the pore-scale modeling techniques is presented in Table 5.…”
Section: Data-driven Modeling Approachesmentioning
confidence: 99%
“…The application of data-driven approaches for the study of West Siberian shales was dedicated mostly to the characterization of geological and petrophysical properties of tight oil reservoirs. With respect to improved and enhanced oil recovery methods, most of the research was dedicated to optimization of hydraulic fracturing techniques [145][146][147][148]. A summary of the pore-scale modeling techniques is presented in Table 5.…”
Section: Data-driven Modeling Approachesmentioning
confidence: 99%
“…Chaikine et al reported that the developed model could predict individual well production with a 14.9% average error which can be decreased exponentially with multiple well aggregations. Other references for hydraulic fracturing design optimization are Mutalova et al [140], Wang et al [141], and Hryb et al [142]. Fracture-interaction studies have been combined with machine learning techniques, such as fracture interference [143] and automated hydraulic fracturing [144].…”
Section: Data Analytics Approachmentioning
confidence: 99%